Preparo e avaliação de catalisadores de dióxido de estanho (SNO2) ou óxido de nióbio (V) (Nb2O5) modificados com metais de transição - Rezende, Carlos Cândido de (2016)
Textile industry uses, in its manufacturing processes, organic dyes which are difficult to be degraded and are daily disposed in natural waters. Once in the environment, dyes may show toxic and/or genotoxic effects in organisms. The total production of dyes worldwide is estimated at 800,000 tons per year and at least 10-15% are discharged into environment by effluents. In this paper, it was synthesized materials based on tin dioxide (SnO2), tin dioxide doped with nickel (Ni-SnO2) and with rhodium (Rh-SnO2), and niobium oxide (V) doped with Rh (Rh-Nb2O5). These materials were prepared through the coprecipitation method using ammonium hydroxide or sodium hydroxide as precipitation agent and pH adjustment. Based on diffuse reflectance, doped materials have presented more intense color than the pure oxides, indicating a change in the values of the band gap. Tin dioxide was doped with 1.1% and 2.3% of Ni and 1% of Rh, 1% and 0.5% of Rh-Na-SnO2, and the niobium oxide (Nb2O5) with 1.6%, 4% and 10% of Rh. The analysis of X-ray diffraction (XRD) of the tin dioxides allowed the identification of the tetragonal structure of cassiterite type (SnO2), confirmed through the JCPDS 041-1445 record. In the doping of Nb2O5 there was the formation of sodium oxide and niobium (Na2Nb4O11, JCPDS 44-60). By Sherrer equation, crystallites diameters are in the nanometer scale. For tin dioxide materials, the Mössbauer spectroscopy of 119Sn indicated the high valency of tin (Sn+4) and that materials with nickel presented a break of symmetry around the tin, indicating the existence of nickel atoms doping the material. Diffuse reflectance results allowed observing that the band gap values are decreased according to the increase of concentration of the doping. In order to define the conditions of Rhodamine B degradation, some tests were performed, using the tin dioxide (SnO2), such as the influence of hydrogen peroxide amount, the influence of dye concentration and the pH variation of the colorant solution. The best conditions for performing the catalytic tests were 0.01 mL of H2O2 50%, concentration of Rhodamine B dye of 10 ppm and pH equal to 6. Tests revealed that for the materials of tin dioxide and niobium oxide (V), both with higher percentage of doping, the color removal was around 50%.